IL11 is elevated in systemic sclerosis and IL11-dependent ERK signalling underlies TGFβ-mediated activation of dermal fibroblasts. (16th February 2021) - Adami, Eleonora; Viswanathan, Sivakumar; Widjaja, Anissa A; Ng, Benjamin; Chothani, Sonia; Zhihao, Nevin; Tan, Jessie; Lio, Pei Min; George, Benjamin L; Altunoglu, Umut; Ghosh, Kakaly; Paleja, Bhairav S; et al.
Abstract: Objectives: Interleukin 11 (IL11) is highly upregulated in skin and lung fibroblasts from patients with systemic sclerosis (SSc). Here we tested whether IL11 is mechanistically linked with activation of human dermal fibroblasts (HDFs) from patients with SSc or controls. Methods: We measured serum IL11 levels in volunteers and patients with early diffuse SSc and manipulated IL11 signalling in HDFs using gain- and loss-of-function approaches that we combined with molecular and cellular phenotyping. Results: In patients with SSc, serum IL11 levels are elevated as compared with healthy controls. All transforming growth factor beta (TGFβ) isoforms induced IL11 secretion from HDFs, which highly express IL11 receptor α-subunit and the glycoprotein 130 (gp130) co-receptor, suggestive of an autocrine loop of IL11 activity in HDFs. IL11 stimulated ERK activation in HDFs and resulted in HDF-to-myofibroblast transformation and extracellular matrix secretion. The pro-fibrotic action of IL11 in HDFs appeared unrelated to STAT3 activity, independent of TGFβ upregulation and was not associated with phosphorylation of SMAD2/3. Inhibition of IL11 signalling using either a neutralizing antibody against IL11 or siRNA against IL11RA reduced TGFβ-induced HDF proliferation, matrix production and cell migration, which was phenocopied by pharmacological inhibition of ERK. Conclusions: These data reveal that autocrine IL11-dependent ERK activity alone or downstream of TGFβ stimulation promotes fibrosis phenotypes in dermal fibroblasts and suggest IL11 as a potential therapeutic target in SSc.